Direct cloning and tetramer staining to measure the frequency of intestinal gluten‐reactive T cells in celiac disease. Issue 10 (15th July 2013) - Bodd, Michael; Ráki, Melinda; Bergseng, Elin; Jahnsen, Jørgen; Lundin, Knut E. A.; Sollid, Ludvig M.
<x xml:space="preserve">Abstract</x> Knowledge of the frequency of disease‐driving CD4+ T cells in lesions of chronic human inflammatory diseases is limited. In celiac disease (CD), intestinal gluten‐reactive CD4+ T cells, which recognize gluten peptides only in the context of the disease‐associated HLA‐DQ molecules, are key pathogenic players. By cloning CD4+ T cells directly from intestinal biopsies of CD patients, we found that 0.5–1.8% of CD4+ T cells were gluten reactive. About half of the gluten‐reactive T cells were specific for either the immuno‐dominant DQ2.5‐glia‐α1a or DQ2.5‐glia‐α2 epitopes, suggesting that direct visualization of gluten‐specific T cells could be possible. Assessed by flow cytometry, tetramer‐positive T cells were present in 10/10 untreated CD patients with a frequency of 0.1–1.2% of CD4+ T cells. Gluten‐specific T cells were also detectable in most treated CD patients (7/10). Moreover, the frequency of gluten‐specific T cells correlated with the degree of histological damage in the gut mucosa as scored by Marsh‐grading, and also with serum IgA anti‐transglutaminase 2 antibody levels. Tetramer staining of gluten‐reactive T cells in biopsy material is a useful tool for future studies of such cells in CD and could also potentially serve as a diagnostic supplement in selected cases.